Studi Analisis Dampak Lalu Lintas Akibat Pembangunan Gedung Fase VII Pasar Raya Kota Padang - Prices, Afrizal Putra; Momon, Momon (Program Studi Teknik Sipil, 2025)
The city of Padang is the capital city of West Sumatra Province which is located on the west coast of the island of Sumatra, in a position between 0°44' and 01°08' South Latitude and between 100°05' and 100°34' East Longitude. The construction of Phase VII Pasar Raya Padang City is located on Jalan M. Yamin, Jalan Sandang Pangan and Jalan Pasar Raya Kampung Jao Village, Padang Barat District. The construction site is in a commercial and office area. The increase in traffic volume due to the development will cause conflict between the amount of traffic generated and the capacity of the roads around Pasar Raya Phase VII, Padang City. This study aims to analyze the impact of traffic around the area due to the development of Pasar Raya Phase VII, Padang City. The analysis carried out includes generation and attraction analysis, analysis of road performance, and analysis of handling traffic impacts on existing traffic conditions, construction and operational periods. The results showed that the performance of the road section in the existing traffic conditions obtained the results of the loading, namely with V/C Ratio ranging from 0.12 to 0.84 with service level A to service level D. Then in traffic conditions during the construction period, namely V/C ratio ranging from 0.16 to 0.88. And finally in operational traffic conditions with V/C ratios ranging from 0.05 to 0.94.